ANALISIS SIMBOL SATANISME PADA VIDEO KLIP BAND DEWA 19 - Rian, Rian; Sudaryanto, Edy; Wibowo, Judhi Hari (Universitas 17 Agustus 1945 Surabaya, 2017)
This research is motivated by the development of the spread of symbols of satanism in the modern era that mushroomed in various mass media, especially video clips to give and deliver messages. One of the top bands named Dewa 19 has symbols associated with symbols of satanism and spread the symbol through the media video clips of the songs of God 19. The focus of this study is the meaning of video clip symbols scattered on each video clip kara band Dewa 19. The theory used is Charles Sanders Peirce Semiotics theory which has a triadic model and trichotomy concept consisting of Representamen, interpretant, and object. The research method used in this research is qualitative research with descriptive type. The results of the research found that the meaning of the symbols scattered in each of the video clips of the band Dewa 19 is the result of the symbolic representation of satanism, among others: Horus's Eye, Pyramid Terpanchung, Chessboard Chess, Photo of Satan Church Founder, God Ra, ANKH SymbolKeywords: semiotics, satanism, Dewa 19, symbols.